Integralus informacijos saugumo valdymo modelis - Jastiuginas, Saulius (Information & Media, 2012)
Saugumo sąvoka yra daugialypė ir nevienareikšmiškai apibrėžiama, saugumas gali būti suprantamas kaip būsena, kuri gali reikšti ir apsisaugojimą nuo pavojaus (objektyvus saugumas), ir saugumo jausmą (subjektyvus saugumas). Siekiant sumažinti neapibrėžtumą, aptariant saugumo sąvoką būtina įvardyti objektą, t. y. kas turi būti (tapti) saugu. Analizuojant informacijos saugumo mokslinių tyrimų problematiką, galima daryti prielaidą, kad pagrindinis objektas, kurį siekiama apsaugoti, yra informacija, tačiau neretai saugumo objektu virsta informacinės technologijos ar informacinės sistemos, kuriomis tvarkoma informacija. Darant esminę mokslinę prielaidą, kad svarbiausias informacijos saugumo objektas yra informacija, tikėtina, kad informacijos saugumas turėtų būti tiriamas kaip sudėtinė informacijos vadybos ir kitų gretutinių informacinių koncepcijų (informacijos išteklių vadybos, informacijos sistemų vadybos, informacijos įrašų vadybos) dalis. Straipsnyje aptariamas tyrimas, įrodantis keliamos mokslinės prielaidos pagrįstumą. Pagrindiniai žodžiai: informacijos saugumas, informacijos saugumo valdymas, informacijos vadyba, informacijos saugumo valdymo modelis. Integral Information Security Management Model Saulius Jastiuginas Summary Analysis of the currently most widely applied means of information security management (methodologies, standards, models) allows finding a growing assimilation of media content, but the frequent information security problems (for example, information security incident growth), show that the existing measures do not provide sufficient information security management. The analysis of information security research problems shows that the main object is to protect the information, but it often becomes the subject of security information technology or information systems that support information processing. A substantial scientific assumption is that the primary object of information security is information, it is likely that information security should be studied as an integral part of information management and the other related concepts (information resource management, information systems management, information, records management). The analysis of the information management has shown that the security component of informa30 tion management is not developed. Scientific insight, emphasizing information as a critical resource organization, poor information management, focus on the resource security becomes a relevant scientific problem and do not provide scientific information security management problems that are apparent on the practical level. The aim of the study was to create a scientific basis for the integral management of information security model that integrates information security management and information management components. The paper deals with the basic information management tools and practices of information security management possibilities. The results of the analysis helped to reduce the gap in research and to develop a theoretical basis for the integral form of information security management model. The proposed theoretical model and the integrated security information management component extend the possibilities of secure information management. The aim of the article was to create a scientific basis for the integral model of information security management that integrates information security management and information management components. The paper analyzes the main information management tools and opportunities to use them for information security management. The results of the analysis helped to reduce the gap in scientific research and to develop a theoretical basis for the integral information security management model.